Meningkatkan Hasil Belajar Siswa Pada Materi Operasi Bilangan Bulat Dengan Menggunakan Model Pembelajaran Matematika Kreatif Di Kelas IV SD Negeri Lelang: Indonesia - Pay, Jesika Vebianti; Ayal, Carolina Selfisina; Takaria, Johannis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main objective of this study was to improve students' learning outcomes in the topic of whole number operations through the use of creative mathematics learning models in class IV SD Negeri Lelang. The method applied in the form of Classroom Action Research was implemented through two cycles of implementation. A total of 16 grade IV students were used as research subjects, consisting of 12 male and 4 female students. Data collection techniques used triangulation, while analysis was carried out qualitatively with a focus on understanding the meaning of the data rather than drawing generalisations. Based on the results of the study, the use of creative mathematics learning models proved effective in improving student learning outcomes. The students' learning completeness increased from an average of 68.75 in cycle I to 74.325 in cycle II. The data provides evidence of the effectiveness of the model in improving students' understanding of whole number operations